Nimesulide inhibits pathogenic fungi: PGE2-dependent mechanisms - de Matos, Rafaelle Fonseca; Mendonça, Lúcia Carla Vasconcelos; da Silva Souza, Kaira Geiliane; Fonseca, Adriana Aparecida Durães; Costa, Elaine Mirla Souza; de Lima, Marcus Vinicius Dias; Vieira, José Maria Dos Santos; de Brito, Mioni Thielli Figueiredo Magalhães; Monteiro, Marta Chagas (Folia microbiologica, 2017)
Certain non-steroidal anti-inflammatory drugs can inhibit fungal growth, fungal prostaglandin E2 production, and enzyme activation. This study aims to investigate the antifungal effect of nimesulide against pathogenic filamentous fungi and yeast. The experiments detailed below were also designed to investigate whether the action is dependent on E2 fungal prostaglandins. Our data showed that nimesulide exhibited potent antifungal activity, mainly against Trichophyton mentagrophytes (ATCC 9533) and Cryptococcus neoformans with MIC values of 2 and 62 μg/mL, respectively. This drug was also able to inhibit the growth of clinic isolates of filamentous fungi, such as Aspergillus fumigatus, and dermatophytes, such as T. rubrum, T. mentagrophytes, Epidermophyton floccosum, Microsporum canis, and M. gypseum, with MIC values ranging from 112 to 770 μg/mL. Our data also showed that the inhibition of fungal growth by nimesulide was mediated by a mechanism dependent on PGE2, which led to the inhibition of essential fungal enzymes. Thus, we concluded that nimesulide exerts a fungicidal effect against pathogenic filamentous fungi and yeast, involving the inhibition of fungal prostaglandins and fungal enzymes important to the fungal growth and colonization.
Keywords: Microbial Sensitivity Tests; Dinoprostone; sulfonamidy; mikrobiální testy citlivosti; Aspergillus fumigatus; dinoproston; Cryptococcus neoformans; Arthrodermataceae; Antifungal Agents; Sulfonamides; antifungální látky; Trichophyton